Technological education and its influence on traditional education - Rivera-Vera, Lisbeth Julissa; Alcívar-Castro, Eddie José (International research journal of management, IT and social sciences, 2024)
Traditional education faces significant challenges in the face of rapid digital evolution, the objective was to evaluate the impact of new technologies on pedagogical practice and its influence on student learning, a deductive approach was used to identify the difficulties faced by both teachers and students when incorporating technology into their school activities. The research was carried out at the Monserrate Álava de Gonzáles Educational Unit, where a structured questionnaire was applied to eighth-grade students, applying quantitative methodology, using numerical data collection and analysis techniques. The result was the importance of continuous training of teachers in educational technology to improve their ability to effectively integrate technology in the classroom. A deductive approach was used to analyze the level of adaptation capacity of the students in the management of educational technology. Highlighting the need for complementary education programs, as well as providing support to develop technological competencies in teachers and students, which will contribute to guaranteeing the successful integration of technology in the educational environment and improving educational quality in general.